The Tuhor Tradition In Marriage Among The South Tapanuli Community The Dialictic Between Custom and Islamic Law - Ahmad Soleh Hasibuan; Sawaluddin Siregar (Universitas Darunnajah Jakarta, Indonesia, 2026)
The tradition of tuhor (bride-price) in the marriage customs of the Tapanuli Selatan community represents a complex intersection between local adat values and Islamic legal principles. This study aims to examine the dynamics of determining the quantity of tuhor through the dialectical relationship between customary norms and Islamic jurisprudence. Employing a qualitative field research approach, data were collected through interviews with religious leaders, adat elders, and community members involved in marriage negotiations. The analysis used a socio-legal framework to reveal the coexistence and tension between customary practices and Islamic legal ethics. The findings indicate that tuhor functions not merely as a material requirement but as a symbol of family honor, social responsibility, and mutual respect between kinship groups. From an Islamic perspective, the amount of tuhor should align with the principle of fairness (‘adl) and should not burden either party. However, in practice, social prestige and local status often influence the determination of its value, leading to disparities between religious ideals and customary expectations. The study concludes that harmonization between adat and Islamic law is essential to ensure that the implementation of tuhor reflects both cultural dignity and the spirit of justice as mandated in Islamic teachings.